FORMULATION AND EVALUATION OF FAST DISSOLVING SUBLINGUAL FILM OF PAROXETINE HYDROCHLORIDE FOR TREATMENT OF DEPRESSION - RITA N WADETWAR; FARHEEN ALI; PRANITA KANOJIYA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Oromucosal route could be an alternative over the conventional route for paroxetine hydrochloride (PXH) as it offers direct systemic delivery, by avoiding extensive first-pass metabolism, which results in poor systemic absorption. The film dissolves quickly when placed in mouth without need of water thus helpful in providing rapid onset of action. Methods: Fast dissolving film of PXH was prepared using Pullulan in various combinations of 32 full factorial design by solvent casting technique. Prepared films were subjected to mechanical, in vitro, and ex vivo characterization. Results: The physicochemical characteristics such as mass uniformity, thickness, surface pH, and folding endurance were found satisfactory. The formulation (F3) containing 4% w/v Pullulan showed maximum release 94.31% and ex vivo permeation 92.67% through goat oral mucosa in 15 min. Uniform drug loading was observed in all the batches with disintegration time <25 s. Fourier transform infrared spectroscopy study revealed the compatibility of drug with polymer. Scanning electron microscopy revealed that there was uniform mixing of all ingredients. Optimized batch F3 was found to be stable for 1 month as no significant changes were observed in % cumulative drug release and weight of film. Conclusion: Pullulan a natural biodegradable polymer allocates good physical property to film. Hydrophilic nature of polymer imparts fast disintegrating property to film.